Determination of cardiovascular risk and vascular age by the Framingham score in patients at the Arzobispo Loayza Hospital - Mayta Calderón, Jean Carlo (2015)
Cardiovascular diseases rank fourth place of disease burden in Peru, and in the last 7 years, the population of high cardiovascular risk has increased. Objective: Determine the cardiovascular risk and vascular age according to the Framingham score in patients attending the "Hospital Nacional Arzobispo Loayza", as well as to determine the most prevalent factor. Furthermore, to determine the clinical characteristics of patients with mild and high risk. Material and Methods: This is a descriptive, observational, cross-sectional study. 238 hospitalized patients in internal medicine wards were surveyed. Variables such as age, gender, diabetes, smoking, BMI and blood pressure were considered. The data were analyzed using SPSS v.21. Results: The highest percentage of the population was found within the mild and high risk categories, with diabetes being the most prevalent factor. The average difference between chronological age and vascular age was 6.9 years. Conclusion: The majority of the population has mild and high risk, thus primary and secondary prevention measures should be taken.